UJI AKTIVITAS ANTIBAKTERI HAND SANITIZER DARI EKSTRAK ETANOL BUNGA ROSELLA (Hibiscus Sabdariffa L) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus - Adiansyah Adiansyah; Siti Maimunah; Elly Nurita Sitorus; Nurul Hazlinda (UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
In Indonesia with a tropical climate, rosella can thrive. Roselle plant (Hibiscus sabdariffa L.) is well known for its petals which can be used as a health drink that can cure various diseases. Roselle flower (Hibiscus sabdariffa L.) contains nutritious substances such as alkaloids, flavonoids, tannins, terpenoids, which have antibacterial properties. The purpose of this study was to determine the antibacterial hand sanitizer ethanol extract of Rosella flower (Hibiscus sabdariffa L) had good quality and stability against Staphylococcus aureus bacteria. This research was experimental, including rosella flower sample collection, simplicia drying, extract making using a rotary evaporator, phytochemical screening, characteristics of the antibacterial activity test preparation of hand sanitizer with agar diffusion method using paper discs. Roselle flower ethanol extract can be made as Hand sanitizer in spray preparations and has antibacterial activity. The difference in the concentration of the ethanol extract is 2.5%, the inhibition zone is 6.8 mm, 5% is the inhibition zone is 7.27 mm, 7.5% is the inhibition zone is 7.72 mm and 10% is 12.35 mm. The ethanolic extract of the Roselle flower (Hibiscus sabdariffa L) can be used as a hand sanitizer preparation. It has antibacterial activity against Staphylococcus aureus bacteria and is the most effective at a concentration of 10% of 12.35 mm.